Fast sequence evolution of Hox and Hox-derived genes in the genus Drosophila. - Casillas, S.; Negre, B.; Barbadilla, A.; Ruiz, A. (BMC Evolutionary Biology, 2006)
It is expected that genes that are expressed early in development and have a complex expression pattern are under strong purifying selection and thus evolve slowly. Hox genes fulfill these criteria and thus, should have a low evolutionary rate. However, some observations point to a completely different scenario. Hox genes are usually highly conserved inside the homeobox, but very variable outside it.We have measured the rates of nucleotide divergence and indel fixation of three Hox genes, labial (lab), proboscipedia (pb) and abdominal-A (abd-A), and compared them with those of three genes derived by duplication from Hox3, bicoid (bcd), zerknüllt (zen) and zerknüllt-related (zen2), and 15 non-Hox genes in sets of orthologous sequences of three species of the genus Drosophila. These rates were compared to test the hypothesis that Hox genes evolve slowly. Our results show that the evolutionary rate of Hox genes is higher than that of non-Hox genes when both amino acid differences and indels are taken into account: 43.39% of the amino acid sequence is altered in Hox genes, versus 30.97% in non-Hox genes and 64.73% in Hox-derived genes. Microsatellites scattered along the coding sequence of Hox genes explain partially, but not fully, their fast sequence evolution.These results show that Hox genes have a higher evolutionary dynamics than other developmental genes, and emphasize the need to take into account indels in addition to nucleotide substitutions in order to accurately estimate evolutionary rates.